Developing Virtual Innovation and Support Networks for In-Service and Pre-Service Teachers - Nicolaou, Anna; Sauro, Shannon; Flogie, Andrej; Gutierrez, Begoña F.; Martinc, Urška; O’Dowd, Robert; Zemljak, Dejan (My University, 2021)
To guide the development of VALIANT’s Virtual Exchange modules, we reviewed academic and policy literature on using online collaborative technologies to best serve the needs of the different populations taking part in VALIANT. This report begins with an exploration of European policy documentation regarding virtual collaboration in teacher education. This is followed by a review of publications which detail the pedagogical justification for using Virtual Exchange in teacher education. The remaining two sections then synthesize research on Virtual Exchange in Initial Teacher Education and research on Virtual Exchange in professional development programmes. Key issues and findings from each of these four sections and their implications for the design and implementation of the VALIANT modules are presented in the conclusion.
Keywords: Virtual collaboration; Teacher education; Virtual exchange